Isolation and characterization of catalase-negative and catalase-weak strains of Campylobacter species, including "Campylobacter upsaliensis," from humans with gastroenteritis. - Taylor, D E (1989)
During 1987 and 1988, nine strains of catalase-negative or -weak Campylobacter species were isolated in Alberta, Canada. DNA hybridization studies demonstrated that seven strains were "Campylobacter upsaliensis," one strain was highly homologous with Campylobacter jejuni DNA, and one strain was a campylobacter unrelated to the other two species. All "C. upsaliensis" strains were hippurate negative, and six of seven were susceptible to cephalothin. The unusual variant of C. jejuni was hippurate positive and cephalothin resistant, whereas the unclassified strain was hippurate negative and resistant to intermediate levels of cephalothin. All patients from whom "C. upsaliensis" was isolated had diarrhea. Five of the patients were children two years old or younger, and two were adults. In this study, all catalase-negative and -weak strains were isolated from stool specimens by using a charcoal-based selective medium containing 32 micrograms of cefaperazone per ml and which was described by Hutchinson and Bolton (D. N. Hutchinson and F. J. Bolton, J. Clin. Pathol. 37:956-957, 1984).